A guarda nacional da província paraense - NUNES, Herlon Ricardo Seixas (Universidade Federal do Pará, 2020)
This article tried to contemplate on some subjects that helped to reveal tensions in the Província Paraense. Discussions, as the national guard’s appearance, his/her legislation and his/her formation, are thematic that compose this work and the object in subject, exactly for provoking debates and inquietudes in the breast of the Província Paraense of the first half of the century XIX. This way, the problematização controls in understanding as certain social subjects - national guards - they were made presents in the breast of the society wrapped up paraense in tensions and relationships of force in a period of intense infra-structural transformations that the own Regency tried operacionalizar. The guard’s national paraense formation, in this context, was constituted as normatização mechanism and adaptation of a pattern comportamental legalistic tax to a society - until then “forgotten” - that had different interests, that space from the simple treatment of the farming to needs tied mercadológicas the Portuguese metropolis.